Musical, language, and reading abilities in early Portuguese readers - Zuk, Jennifer; Andrade, Paulo E.; Andrade, Olga V.; Gardiner, Martin F.; Gaab, Nadine (Frontiers in Psychology, 2013)
Early language and reading abilities have been shown to correlate with a variety of musical skills and elements of music perception in children. It has also been shown that reading impaired children can show difficulties with music perception. However, it is still unclear to what extent different aspects of music perception are associated with language and reading abilities. Here we investigated the relationship between cognitive-linguistic abilities and a music discrimination task that preserves an ecologically valid musical experience. 43 Portuguese-speaking students from an elementary school in Brazil participated in this study. Children completed a comprehensive cognitive-linguistic battery of assessments. The music task was presented live in the music classroom, and children were asked to code sequences of four sounds on the guitar. Results show a strong relationship between performance on the music task and a number of linguistic variables. A principle component analysis of the cognitive-linguistic battery revealed that the strongest component (Prin1) accounted for 33% of the variance and Prin1 was significantly related to the music task. Highest loadings on Prin1 were found for reading measures such as Reading Speed and Reading Accuracy. Interestingly, 22 children recorded responses for more than four sounds within a trial on the music task, which was classified as Superfluous Responses (SR). SR was negatively correlated with a variety of linguistic variables and showed a negative correlation with Prin1. When analyzing children with and without SR separately, only children with SR showed a significant correlation between Prin1 and the music task. Our results provide implications for the use of an ecologically valid music-based screening tool for the early identification of reading disabilities in a classroom setting.